2016
DOI: 10.4254/wjh.v8.i20.827
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of non-alcoholic fatty liver disease: From susceptibility and nutrient interactions to management

Abstract: Genetics plays an important role in determining the susceptibility of an individual to develop a disease. Complex, multi factorial diseases of modern day (diabetes, cardiovascular disease, hypertension and obesity) are a result of disparity between the type of food consumed and genes, suggesting that food which does not match the host genes is probably one of the major reasons for developing life style diseases. Non-alcoholic fatty liver is becoming a global epidemic leading to substantial morbidity. While var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Finally, genome‐wide association studies showed an association between the HSD17B13 locus and fatty liver disease (http://www.ncbi.nlm.nih.gov/pmc/?term=hsd17b13%20NAFLD). (40, 5056) However, all these studies are based on HSD17B13 mRNA expression, which could not always reflect the protein expression or activity of the enzyme. Further studies are required to clarify how expression and activity of HSD17B13 are modulated with FLD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genome‐wide association studies showed an association between the HSD17B13 locus and fatty liver disease (http://www.ncbi.nlm.nih.gov/pmc/?term=hsd17b13%20NAFLD). (40, 5056) However, all these studies are based on HSD17B13 mRNA expression, which could not always reflect the protein expression or activity of the enzyme. Further studies are required to clarify how expression and activity of HSD17B13 are modulated with FLD.…”
Section: Discussionmentioning
confidence: 99%
“…Whole exome sequencing studies performed on obese Caucasian participants with NAFLD have revealed deleterious mutations in Bardet-Biedl syndrome 1 gene as well as the Melanocortin 3 receptor gene[58]. In 2008, the first genome wide association study was published; it examined hepatic triacylglycerol (HTAG) accumulation and identified association with increased HTAG and the PNPLA3 gene[59].…”
Section: Geneticsmentioning
confidence: 99%
“…Apart from environmental factors various studies have now confirmed the role of genetics in conferring susceptibility to the disease. Diseases with complex traits including NAFLD result from interactions between environment and polygenic genetic susceptibility made up of many independent modifiers[ 8 ]. Family aggregation, studies on twins and differences in susceptibility and progression suggest a significant heritable component to NAFLD that may be classified under “common disease-common variant” hypothesis[ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carrier of the minor allele and 148M was associated with a twofold increase in HTGC (Hepatic triglyceride content)[ 10 ]. Subsequent to this, the SNP was replicated in almost all the ethnicities successfully[ 8 ]. Further, two exome wide association studies[ 11 , 12 ] carried out independently in African-American and Norwegian ethnicities identified that a variant rs58542926 (p.E167K) in TM6SF2 gene was associated with susceptibility to NAFLD, influencing total cholesterol levels and enhanced risk of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%